What Can Be Learned From Crowdsourced Population Asparagus Urinary Odor Kinetics?. (23rd April 2019) - Facius, Axel; Atkinson, Linda A.; Hanna, Kelly; Coombes, Mai Chi; Lahu, Gezim; Wagner, John A.
Abstract : Asparagus consumption is associated with the production of malodorous urine. Interindividual variability was previously characterized by an American Society for Clinical Pharmacology and Therapeutics crowdsourced study. To further characterize urinary odor kinetics, we conducted a study with consenting participants from Takeda Pharmaceutical International Company. The participants were randomized to consume a specified number of asparagus spears and asked to record urine odor. A kinetic‐pharmacodynamic model characterized the data from both the newly conducted Takeda study ( N  = 42) and the previously analyzed American Society for Clinical Pharmacology and Therapeutics studies (total N  = 139). The updated model included the identification of an absorption process with a half‐life of 25 minutes. We estimated the elimination half‐life of the asparagus effect on malodorous urine to be 7.2 hours, which was 44% longer in our study. We built on previous experience using an improved R‐Shiny app for conducting the crowdsourcing experiment, further demonstrating the utility of this population kinetics approach in organizational and educational settings.